Mechanisms for pattern specificity of deep-brain stimulation in Parkinson's disease - Velarde, M.O.; Mato, G.; Delavalle, D. (Public Library of Science, 2017)
Fil: Velarde, M.O. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina